2021
DOI: 10.1016/j.metabol.2021.154888
|View full text |Cite
|
Sign up to set email alerts
|

ApoA-I mimetics favorably impact cyclooxygenase 2 and bioactive lipids that may contribute to cardiometabolic syndrome in chronic treated HIV

Abstract: We investigated whether apolipoprotein A-I (apoA-I) mimetic peptides 4F and 6F can be a novel therapeutic strategy to reduce blood and gut bioactive lipids, proinflammatory effects of endotoxin (LPS) and aberrant activation of cyclooxygenase 2 (COX-2) as instigators of increased risk for cardiometabolic disease in chronic treated HIV. Methods: We used two humanized murine models of chronic treated HIV infection (n = 109 mice) and gut explants from HIV infected (n = 10) persons to determine whether Tg6F and 4F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Homogenates were centrifuged at 16,000 g for 10 min and supernatants were then cryopreserved at -80 °C for viral titer in Vero-E6 cells. For tissue lysates that were used for protein measurements, 50-100 mg of lung tissue samples were placed in 2 ml screwcap dissociation tubes with ceramic beads (Precellys) and were mechanically dissociated in 57 T-PER tissue protein extraction Reagent at power 5,000 rpm leaving samples to cool on ice between 1-2 repeated 20-second cycles as previously described (Daskou et al, 2021).…”
Section: Mouse Tissue Processingmentioning
confidence: 99%
“…Homogenates were centrifuged at 16,000 g for 10 min and supernatants were then cryopreserved at -80 °C for viral titer in Vero-E6 cells. For tissue lysates that were used for protein measurements, 50-100 mg of lung tissue samples were placed in 2 ml screwcap dissociation tubes with ceramic beads (Precellys) and were mechanically dissociated in 57 T-PER tissue protein extraction Reagent at power 5,000 rpm leaving samples to cool on ice between 1-2 repeated 20-second cycles as previously described (Daskou et al, 2021).…”
Section: Mouse Tissue Processingmentioning
confidence: 99%
“…Kelesidis and colleagues [ 49 ■ , 50 ■ , 51 ■ ] used two humanized mouse models of HIV infection, as well as gut explants from ten uninfected and ten HIV-infected men without evident morbidity to study the chronic inflammatory response in mice and humans on ART with no detectable HIV in blood. The mice were either infected with HIV or not, either treated with ART to reduce viral load to undetectable levels in blood or the mice did not receive ART, and either received a concentrate of transgenic tomatoes expressing the 6F peptide (Tg6F) that was added to their chow or they received a control transgenic tomato concentrate without the 6F peptide.…”
Section: Gut-derived Lipopolysaccharide Oxidized Lipids and Apoa-i Mi...mentioning
confidence: 99%
“…Daskou et al . [ 50 ■ ] found that HIV infected humanized mice on ART and the control transgenic tomato concentrate had higher levels of plasma and gut bioactive lipids [particularly lipids derived from the cyclooxygenase (COX) pathway] compared to HIV infected humanized mice on ART and Tg6F. Ex vivo, the LPS stimulated production of COX-2 protein and associated secretion of bioactive lipids in gut explants from HIV infected persons on ART were reduced by the addition of 6F or 4F peptides [ 50 ■ ].…”
Section: Gut-derived Lipopolysaccharide Oxidized Lipids and Apoa-i Mi...mentioning
confidence: 99%